2015
DOI: 10.1016/j.breast.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Features of aggressive breast cancer

Abstract: Identification of these factors and understanding their contribution to the aggressiveness of MBC and disease progression may lead to more personalized treatment in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…30 Several studies have reported that presence of genetic factors as mutations and polymorphisms (BRCA1/2, TP53, PTEN and MIF) plays an important role in the development of BC, as well as proinflammatory cytokines, like MIF. 25,31 The human MIF gene is characterized by the presence of a single nucleotide polymorphism (-173 G > C) and a microsatellite repeat (-794 CATT) both in the promoter region. 11 The involvement of MIF alleles in the development of cancer was first associated and described in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30 Several studies have reported that presence of genetic factors as mutations and polymorphisms (BRCA1/2, TP53, PTEN and MIF) plays an important role in the development of BC, as well as proinflammatory cytokines, like MIF. 25,31 The human MIF gene is characterized by the presence of a single nucleotide polymorphism (-173 G > C) and a microsatellite repeat (-794 CATT) both in the promoter region. 11 The involvement of MIF alleles in the development of cancer was first associated and described in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray analyses identified the triple-negative breast cancer (ER-, PR- and HER2-negative) as a clinically heterogeneous malignancy and the most aggressive BCa subtype that is characterised by high rates of tumour recurrence and poor overall survival. Aggressive phenotype of TNBC defined by poor disease-free survival, high recurrence rate and shortened time of overall survival is connected with biological and clinical factors, including high nuclear grade, high histological grade, high genomic instability, loss of suppressor genes, as well as gain of migratory, invasive and stem cell-like properties of cancer cells (Arpino et al 2015). …”
Section: Triple-negative Breast Cancer—molecular Featuresmentioning
confidence: 99%
“…In a survey, an estimated 232,670 women were expected to be diagnosed with breast cancer, and 40,000 deaths expected in 2014 [5]. In Europe in 2012, an estimated 463,800 new breast cancer cases and breast cancer-related deaths of 131,200 were recorded [6]. …”
Section: Introductionmentioning
confidence: 99%